If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 + 13 * 0.35x = 70 Multiply 13 * 0.35 36 + 4.55x = 70 Solving 36 + 4.55x = 70 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 4.55x = 70 + -36 Combine like terms: 36 + -36 = 0 0 + 4.55x = 70 + -36 4.55x = 70 + -36 Combine like terms: 70 + -36 = 34 4.55x = 34 Divide each side by '4.55'. x = 7.472527473 Simplifying x = 7.472527473
| 36*13*0.35*x=70 | | 2(z+2)+4z=28 | | 3ab+7ab-12ab= | | 5y-2=35 | | -9y+7-8y^2=0 | | -2y-(y-5/8)-5y=3y-3/4 | | y=-4x^2+24x-25 | | 5x-x+9x= | | 2x+30=2 | | x^2+3x-bx-2b=0 | | 2(x-1)=4x-13 | | 9y+4=8y-3 | | 7=ln(x+3) | | 7=lnx+3 | | 2(z+1)+3=17 | | 3y-10=6x | | x^7=2x+5 | | 3y=-6x+10 | | x^6+4x^5-1=0 | | 2(z+5)= | | 7x-10=5y | | 5x+20(x-3)=65 | | 3y^2+13y=10 | | x+30=50 | | x-20=70 | | 3-2(x-5)=21 | | (y-6)(y+1)=4 | | 18+3(4-x)=-4(2x+5)+6 | | -6+x^2=-6x | | -3+m^2=-5m | | 2(5-3n)+8=4+5n | | -9+6m^2=-7m |